2011
DOI: 10.1258/ijsa.2011.011040
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic scoring tool for identification of patients at high and low risk of death from HIV-associated Pneumocystis jirovecii pneumonia

Abstract: A prognostic scoring tool (PST) was created to aid prediction of outcome from HIV-associated Pneumocystis jirovecii pneumonia (PCP) using data obtained from 577 episodes of PCP among 540 patients presenting to a specialist HIV treatment centre in London, UK. It used risk factors identifiable at/soon after hospitalization, previously identified as being associated with mortality: repeat episode of PCP, patient's age, haemoglobin (Hb) and oxygen partial pressure (PaO(2)) on admission, presence of medical co-morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Our results are consistent with previous data for HIV-positive patients that mortality was influenced by respiratory failure, high lactate dehydrogenase, low serum albumin, concomitant bacterial infection, and a need for mechanical ventilation [ 4 , 6 , 7 , 22 24 ]. Many other findings in this meta-analysis were novel and deserve further discussion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous data for HIV-positive patients that mortality was influenced by respiratory failure, high lactate dehydrogenase, low serum albumin, concomitant bacterial infection, and a need for mechanical ventilation [ 4 , 6 , 7 , 22 24 ]. Many other findings in this meta-analysis were novel and deserve further discussion.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the pooled overall mortality for non-HIV patients with PCP was 30.6%, which was significantly higher than previously reported mortality rate in HIV-positive patients. The present data confirms the results of previous studies that HIV-negative patients with PCP have different prognosis from the HIV-positive ones [ 7 , 13 , 24 ]. There are several possible explanations for the poorer outcomes in non-HIV PCP.…”
Section: Discussionsupporting
confidence: 93%
“…There are few recent data evaluating clinical risk factors for death during an acute OI in the developed world and recently published studies still often include patients treated in the pre-ART era 13,14 . Our results are consistent with earlier studies in PCP and cryptococcal meningitis that showed that markers of more advanced HIV disease such as low albumin 15 , hemoglobin 16,17 , and total lymphocyte count 18 predicted mortality.…”
Section: Discussionmentioning
confidence: 99%
“…An association of this comorbidity factor with an increased risk for death has already been reported ( 24 , 25 ). Several other clinical parameters were reported to be predictors for death caused by PCP in HIV-infected patients ( 26 ), and a scoring tool was recently proposed ( 27 ). Host polymorphisms within receptors involved in the immune response have also been reported to be related to P. jirovecii infection ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%